2011
DOI: 10.1111/j.1420-9101.2011.02287.x
|View full text |Cite
|
Sign up to set email alerts
|

The decoupling between genetic structure and metabolic phenotypes in Escherichia coli leads to continuous phenotypic diversity

Abstract: To assess the extent of intra-species diversity and the links between phylogeny, lifestyle (habitat and pathogenicity) and phenotype, we assayed the growth yield on 95 carbon sources of 168 Escherichia strains. We also correlated the growth capacities of 14 E. coli strains with the presence/absence of enzyme-coding genes. Globally, we found that the genetic distance, based on multilocus sequence typing data, was a weak indicator of the metabolic phenotypic distance. Besides, lifestyle and phylogroup had almost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 75 publications
2
33
0
Order By: Relevance
“…Moreover, it has been reported that the survival of E. coli is also greatly influenced by previous exposure to stress (19). Thus, beyond the variance related to the design of experiments, the obtained results also illustrate the extensive genetic and phenotypic diversity exhibited within E. coli populations, which could explain the different survival abilities in aquatic environments (3,8,23,24).…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…Moreover, it has been reported that the survival of E. coli is also greatly influenced by previous exposure to stress (19). Thus, beyond the variance related to the design of experiments, the obtained results also illustrate the extensive genetic and phenotypic diversity exhibited within E. coli populations, which could explain the different survival abilities in aquatic environments (3,8,23,24).…”
mentioning
confidence: 73%
“…Because E. coli populations have extensive genetic and phenotypic diversities (3,8,23,24), we tried to explain these different survival abilities by studying the genotypic and phenotypic traits involved in strain persistence in aquatic environments. The presence of an E. coli genotype related to persistent and naturalized strains was already described in temperate and tropical freshwater conditions (15,17,26,42).…”
Section: Discussionmentioning
confidence: 99%
“…Such intraspecies diversity of the growth rate in different media (40,41) and of the RpoS level (42,43) has been reported in other sets of E. coli strains, with no link to the commensal or pathogenic origin of the strains concerned being found. Studies of growth yield on 95 carbon sources in 168 Escherichia strains also demonstrated a high level of diversity that was not structured into groups but that was continuous, with the lifestyle of the strains having almost no impact on growth yield (44). Natural isolates of E. coli have been shown to display various endogenous oxidative stresses when grown in urine, regardless of their origin or pathogenic potential (37).…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial metabolism is arguably the most promising model system for such an endeavour: the ability to metabolize different nutrient sources always remains an essential determinant of bacterial fitness 2 , and flux balance analysis (FBA) has been established as a robust and reliable modeling framework for the prediction of this ability 7 . Experimental growth data indicates that genetic distance, based on multilocus sequence typing data, is a weak indicator of how similar two E. coli strains are in terms of the carbon sources they can metabolize 1 . Similarly, a computational analysis of automatically generated metabolic models for hundreds of species suggested that withinspecies phenotypic divergence is almost instantaneous, while divergence between genera is gradual or "clock-like" 2 .…”
Section: Introductionmentioning
confidence: 99%
“…
AbstractEven closely related prokaryotes show an astounding diversity in their ability to grow in different nutritional environments 1,2 ; more fundamentally, it is unknown what fraction of metabolic adaptations are indeed complex. Here, we use metabolic network simulations to show that all 3,363 phenotypic innovations observed in the evolutionary history of 53 E. coli strains arose through the acquisition of a single DNA segment; while we found no evidence for the contribution of selectively neutral processes, 10.6% of adaptations to previously unviable environments relied on the support of DNA acquisitions on earlier phylogenetic branches.
…”
mentioning
confidence: 99%